Local area network architecture design at Nurul Jalal Islamic Boarding School, North Jakarta - Sitanggang, Andri Sahata; Syafariani, R. Fenny; Hasti, Novrini; Sari, Febilita Wulan; Pasya, Dhara (International Journal of Advances in Applied Sciences, 2024)
A computer network is a telecommunications network that allows computers to communicate with each other by exchanging data. At Nurul Jalal Islamic Boarding School, they have taken advantage of advances in computer network technology, but have not been fully connected properly. Therefore, in this research, a local area network (LAN) architecture that is connected to speedy internet will be built and developed. The design of this network architecture includes designing a connection to the internet speedy network and designing a computer lab architecture that is connected to the network at the Nurul Jalal Islamic Boarding School. This study aims to design the existing technology with the system and add technologies and systems that do not yet exist so that they can be integrated into a computer network connected to the speedy internet network. It is hoped that this research will help teachers and students of Nurul Jalal Islamic Boarding School in exploring information so that it can help effective and efficient learning.